2008
DOI: 10.1159/000144073
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Rapid Decline in Mini Mental State Examination in Clinical Practice for Prognosis in Alzheimer’s Disease

Abstract: Background: Given the poorer prognosis of Alzheimer’s disease (AD) patients with rapid cognitive decline (RCD), there is a need for a clinical assessment tool to detect these patients. Objective: To investigate if there is a Mini Mental State Examination (MMSE) threshold of decline during 6 months of follow-up which predicts a worse disease progression at the 2-year follow-up. Then, to propose a feasible definition of RCD for routine clinical practice. Methods: Data from 565 community-dwelling AD patients recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 41 publications
2
32
1
5
Order By: Relevance
“…Several studies of Alzheimer disease progression have been conducted using MMSE as the outcome measure. Most of those studies 8,20,36,37,40,[44][45][46] found a strong relation between lower baseline MMSE and worse disease outcomes. Among those studies, the baseline MMSE ranged from 17.6 to 25.2.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of Alzheimer disease progression have been conducted using MMSE as the outcome measure. Most of those studies 8,20,36,37,40,[44][45][46] found a strong relation between lower baseline MMSE and worse disease outcomes. Among those studies, the baseline MMSE ranged from 17.6 to 25.2.…”
Section: Discussionmentioning
confidence: 99%
“…A recent consensus paper (Soto et al, 2008a) sought to establish a definition of rapid cognitive decline, with the authors proposing "the loss of 3 points or greater in MMSE during six months" . In their paper the authors noted that only a few studies had tried to define rapid cognitive decline: in an earlier paper, Soto et al (2005) proposed a 4 point or greater loss on the MMSE within 6 months and the loss of at least 1 more point on the MMSE during the following six months; Carcaillon et al (2007), in their bid to find a significant threshold of decline associated with a higher mortality rate, proposed a loss of 3 points or greater per year on the MMSE; Soto et al (2008b) concluded that the loss of 4 points or more in the MMSE during the first 6 months of follow-up was a predictor of a worse clinical course of AD. Two later papers give a definition of rapid cognitive decline based on the MMSE: Doody et al (2010) who used the same definition as in a previous study (Doody et al, 2001), dividing patients into slow progressors (decline of less than 2 points per year on the MMSE), intermediate progressors (2 to 4 points per year) and rapid progressors (≥5 points per year); and Musicco et al (2010) who considered the time-dependent probability of losing 5 points on the MMSE over two years as rapid disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in the total scores of the Chinese version of Mini-Mental State Examination (C-MMSE) [27,28] and Chinese version of Disability assessment for dementia score (C-DAD) [29] were used as secondary outcomes. Outcome measurements were carried out during the study visits at weeks 0 (baseline), 12 (half of treatment), 24 (end of treatment) and 30 (end of observation period).…”
Section: Outcome Measurements and Its Assessmentmentioning
confidence: 99%